Left ventricle geometry affects coronary flow reserve in diabetic patients - Gülhan Yüksel Kalkan; Mustafa Gur; Zafer Elbasan; Ahmet Oytun Baykan; Osman Kuloğlu; Durmuş Yıldıray Şahin; Taner Şeker; Filiz Ekşi Haydardedeoğlu; Ömer Şen; Hakan Uçar; Sinan Kırım; Murat Çaylı (KARE Publishing, 2015)
Objectives: The aim of this study was to investigate the association between coronary flow reserve (CFR) and left ventricle (LV) geometric patterns in patients with newly-diagnosed diabetes mellitus (DM). Study design: We studied 116 patients with newly-diagnosed DM and 31 healthy control subjects. Echocardiographic examination was performed on all subjects. Four different geometric patterns were identified in diabetic patients, according to LV mass index (LVMI) and relative wall thickness (RWT) [NG: Normal geometry; CR: Concentric remodeling; EH: Eccentric hypertrophy; CH: Concentric hypertrophy]. CFR was calculated as the hyperemic to resting coronary diastolic peak velocities ratio. Results: Compared with controls, CFR was decreased in diabetic patients (p<0.05). The lowest CFR values were observed in the CH group compared with control and other groups (p<0.05, for all). Also, CFR values of the CR and EH groups were lower than NG and the control group (p<0.05, for all). CFR was associated with LV geometry (r=-0.449, p=0.001), LVMI (r=-0.401, p<0.001), RWT (r=-0.247, p=0.008), HbA1c (r=-0.576, p<0.001) and mitral valve E/A ratio (r=0.239, p=0.01) in bivariate analysis. CFR was independently associated with LV geometry (β=-0.449, p<0.001), LVMI (β=-0.192, p=0.016), and HbA1c (β=-0.576, p<0.001) in multivariate analysis. Conclusion: CFR was impaired in newly-diagnosed DM. The degree of this deformation increases from normal geometry towards to concentric hypertrophy. This condition suggests that myocardial structural remodeling due to diabetes might be effective on CFR.